Renal Denervation: Results of a Single-Center Cohort Study - Luetkens, J. A.; Wilhelm, K.; Düsing, R.; Woitas, R. P.; Thomas, D.; Hundt, F.; Doerner, J.; Schild, H. H.; Nähle, C. P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To investigate the effect of renal denervation on office-based and 24-h ambulatory blood pressure measurements (ABPM) in a highly selective patient population with drug-resistant hypertension.Materials and Methods: Patients with drug resistant hypertension eligible for renal denervation were included in the study population. Office blood pressure and ABPM were assessed prior to and after renal denervation. To detect procedure related renal or renal artery damage, magnetic resonance imaging (MRI) and angiography (MRA) were performed pre-interventional, one day post-interventional, and one month after renal denervation.Results: Mean follow-up time between renal denervation and blood pressure re-assessment was 9.5 ± 3.9 months. Between August 2011 and March 2013, 17 patients prospectively underwent renal denervation. Pre-interventional mean office blood pressure and ABPM were 177.3 ± 20.3/103.8 ± 20.4 mmHg and 155.2 ± 20.5/93.7 ± 14.5 mmHg, respectively. Post-interventional, office blood pressure was significantly reduced to 144.7 ± 14.9/89.5 ± 12.1 (p < 0.05). ABPM values remained unchanged (147.9 ± 20.3/90.3 ± 15.6, p > 0.05). The number of prescribed antihypertensive drugs was unchanged after renal denervation (4.7 ± 2.0 vs. 4.2 ± 1.2, p = 0.18). No renovascular complications were detected in follow-up MRI.Conclusion: After renal denervation, no significant decrease in ABPM was observed. These results may indicate a limited impact of renal denervation for drug resistant hypertension.Key Points:• Renal denervation showed no significant effects on 24-h ambulatory blood pressure measurements.• A significant decrease in office blood pressure measurements may be explained by a potential detection bias.• Renal artery alterations were not observed on follow-up MRI scans.Citation Format:• Luetkens J. A., Wilhelm K., Düsing R. et al. Renal Denervation: Results of a Single-Center Cohort Study. Fortschr Röntgenstr 2015; 187: 36 – 41
Keywords: renal arteries; ablation procedures; hypertension